2021
DOI: 10.1371/journal.pcbi.1009674
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical relationship between speed and accuracy in olfactory figure-background segregation

Abstract: In natural settings, many stimuli impinge on our sensory organs simultaneously. Parsing these sensory stimuli into perceptual objects is a fundamental task faced by all sensory systems. Similar to other sensory modalities, increased odor backgrounds decrease the detectability of target odors by the olfactory system. The mechanisms by which background odors interfere with the detection and identification of target odors are unknown. Here we utilized the framework of the Drift Diffusion Model (DDM) to consider p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…The behavioral setup may be important for setting limits on an animal’s reaction time. Shorter reaction times have been reported in task setups different from ours [ 20 22 ], but reaction times were similar to ours in studies with similar behavioral setups as ours, with head restraints and choice reporting using left versus right licks [ 18 , 23 ]. With similar behavioral setups, longer reaction times were also reported in nonolfactory tasks [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The behavioral setup may be important for setting limits on an animal’s reaction time. Shorter reaction times have been reported in task setups different from ours [ 20 22 ], but reaction times were similar to ours in studies with similar behavioral setups as ours, with head restraints and choice reporting using left versus right licks [ 18 , 23 ]. With similar behavioral setups, longer reaction times were also reported in nonolfactory tasks [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown the latency depends on the difficulty of the olfactory task [ 19 , 20 ]. While these earlier studies reported faster reaction times, a recent study [ 18 ] in which mice were trained to report the presence of 1 target odor within a background of other many other odors, reported reaction times similar to those in the present study (approximately 500 ms). The behavioral setup may be important for setting limits on an animal’s reaction time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Cntnap2 −/− mice have multiple circuit deficits that might affect their capability to detect odors in the presence of strong novel background odors. Although we found that increased variability in the Cntnap2 −/− mice glomerular responses was not large enough to affect classifiers’ performances, increased variability in other downstream neural structures could affect the performance, resulting in the lower performance of Cntnap2 −/− mice 65 . The lack of CNTNAP2 causes a broadening of the transmitted action potential resulting in enlarged neurotransmitter release 66 which might cause excessive activation by strong background odors, masking the target odors.…”
Section: Discussionmentioning
confidence: 57%
“…Beyond discriminating odors, the olfactory system also needs to detect and identify odors in the presence of background mixtures. To probe this ability, we tested sFlt1 mice on an olfactory figure-background segmentation task (Rokni et al, 2014; Lebovich et al, 2021). Mice were trained to perform a task, in which they were required to report whether presented mixtures contained a target odorant (see methods).…”
Section: Resultsmentioning
confidence: 99%